The relationship between knowledge capital, spillover effects and labor productivity - Süalp Mustafa Nedim; Durmaz, Cemil Faruk (My University, 2016)
In growth literature the part and the variations of the growth rates unexplained by the changes in the amount of labor and capital, named as Solow Residual, has been continuing to be one of the main concerns. Technological advances and improvements in human capital have been the main candidates in investigating the sources of the unexplained part of the growth phenomenon. However the channels through which technology is transferred among countries still need more investigation. Most part of the literature is focused on the Total Factor Productivity (TFP), the main determinants of which are considered to be the research and development (R & D) and human capital. More recently spillover effects as the way to transfer the technology through the import of capital and Foreign Direct Investment (FDI) have become the central theme. Spillover effects through capital goods imports and domestic R&D capital stock on labor productivity are empirically investigated in this study for 23 countries between 2002 and 2011. Results of panel data analysis indicated that technology transfer is significant and positive for a large and heterogeneous sample. However, capital goods imports do not cause a knowledge transfer from G7 economies to countries with relatively and significantly lower level of productivity. The paper is expected to contribute the literature by using labor productivity instead of total factor productivity when the effects of externalities are investigated in samples with different set of countries.
Keywords: Total Factor Productivity,Labor Productivity,R&D Capital,Spillover Effects